Thermoelectric properties of Nb-doped SrTiO3 films prepared by co-sputtering - Kim, Jinseo; Duy, Le Thai; Lee, Sang Yeon; Ko, Minhwan; Seo, Hyungtak (Journal of Asian Ceramic Societies, 2020)
SrTiO3 (STO), a member of perovskite structure materials, exhibits a large thermoelectric figure of merit at high temperatures. Theoretically, its property can be significantly improved by niobium (Nb) dopant. So far, the synthesis method of Nb-doped STO and the evaluation of their thermoelectric properties at low temperatures have not been explored fully. Here, our development of highly Nb-doped STO films using the co-sputtering with STO and Nb targets at room temperature (298 K) is introduced. A rapid annealing process (30 min, at 1073 K) is applied to further crystallize these films. Through measurements at 300 ~ 600 K, a significant improvement of the thermoelectric performance of STO films upon 2% Nb-doping is observed. Particularly, the working temperature of Nb-doped STO begins at 350 K instead of 475 K of STO. The figure of merit of Nb-doped STO can reach 0.53 at 600 K. Through TEM-EDS and TOF-SIMS characterizations, the mechanism of Nb-doping effect on the STO properties is revealed and discussed in detail. Our doping method at room temperature is potential, as compared to other synthesis methods, regarding the uniform incorporation of Nb dopants in STO films. Overall, our work showed another way for further improvement of perovskite-based thermoelectric materials.
Keywords: High temperature; Perovskite structures; Synthesis method; Thermo-Electric materials; Thermoelectric figure of merit; Thermoelectric performance; Thermoelectric properties; Working temperatures; co- sputtering; doping; niobium; SrTiO3; thermoelectric